2017
DOI: 10.1002/hed.25033
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting operative time in robotic thyroidectomy

Abstract: Body habitus and clinical nodal status in the central compartment should be considered in deciding the indications for robotic thyroidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 36 publications
0
14
0
Order By: Relevance
“…There was no apparent steep learning curve although we might still be on the learning curve because this is our early case series; we have performed more than 700 robotic or endoscopic thyroidectomies via gasless transaxillary and postauricular facelift approaches since 2005, [26][27][28][29][30][31][32] and in our series using the gasless trans-axillary approach, the learning curve was about 35 cases. 34 Alternatively, our substantial experience of robotic and endoscopic thyroidectomy may be related to the absence of a steep learning curve in the transoral thyroidectomy series.…”
Section: Discussionmentioning
confidence: 99%
“…There was no apparent steep learning curve although we might still be on the learning curve because this is our early case series; we have performed more than 700 robotic or endoscopic thyroidectomies via gasless transaxillary and postauricular facelift approaches since 2005, [26][27][28][29][30][31][32] and in our series using the gasless trans-axillary approach, the learning curve was about 35 cases. 34 Alternatively, our substantial experience of robotic and endoscopic thyroidectomy may be related to the absence of a steep learning curve in the transoral thyroidectomy series.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Song et al [30] scrutinized factors affecting operative time in robotic thyroidectomy and reported that BMI ≥ 23 kg/m 2 and central compartment dissection were both independent risk factor for prolonged operative time. Moreover, Kandil et al [20] reported longer operative time in obese patients, either considering the flap creation and console time.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have described BABA methods, including how to make the BABA flap (2)(3)(4)10). BABA flap creation generally requires 30-40 minutes, increasing total operation time (5)(6)(7)(8). Appropriate training for BABA flap creation is very important for the successful implementation of BABA surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The borders of the flap are from the bilateral axillae and breasts to the anterior neck up to the thyroid cartilage superiorly and the medial border of the sternocleidomastoid (SCM) muscle laterally (4). The mean time required to create a BABA flap has been reported to range from 30 to 40 minutes (5)(6)(7), accounting for a large portion of the operation time required for thyroid surgery using BABA (8). Thus, creation of a proper BABA flap is important for the success of BABA thyroid surgery, whether performed endoscopically or robotically.…”
Section: Introductionmentioning
confidence: 99%